MAP2K1 and MAP3K1 mutations in langerhans cell histiocytosis. Issue 6 (31st March 2015) - Nelson, David S.; van Halteren, Astrid; Quispel, Willemijn T.; van den Bos, Cor; Bovée, Judith V.M.G.; Patel, Bhumi; Badalian‐Very, Gayane; van Hummelen, Paul; Ducar, Matthew; Lin, Ling; MacConaill, Laura E.; Egeler, R. Maarten; et al.
Abstract : Langerhans cell histiocytosis (LCH) is now understood to be a neoplastic disease in which over 50% of cases have somatic activating mutations of BRAF . However, the extracellular signal‐related (ERK) pathway is activated in all cases including those with wild type BRAF alleles. Here, we applied a targeted massively parallel sequencing panel to 30 LCH samples to test for the presence of additional genetic alterations that might cause ERK pathway activation. In 20 BRAF wild type samples, we found 3 somatic mutations in MAP2K1 ( MEK1 ) including C121S and C121S/G128D in the kinase domain, and 56_61QKQKVG>R, an in‐frame deletion in the N‐terminal regulatory domain. All three variant proteins constitutively phosphorylated ERK in in vitro kinase assays. The C121S/G128D and 56_61QKQKVG>R variants were resistant to the mitogen‐activated protein kinase kinase (MEK) inhibitor trametinib in vitro. Within the entire sample set, we found 3 specimens with mutations in MAP3K1 ( MEKK1 ), including two truncation mutants, T779fs and T1481fs; T1481fs encoded an unstable and nonfunctional protein when expressed in vitro. T779fs was present in a specimen carrying BRAF V600E. The third variant was a single nucleotide substitution, E1286V, which was fully functional and is likely a germline polymorphism. These results indicate that LCH cells can harbor additional genetic alterations in the RAS‐RAF‐MEK pathway which, in the case of MAP2K1, may be responsible for ERK activation in a wild type BRAF setting. The resistance of some of these variants to trametinib may also have clinical implications for the combined use of RAF and MEK inhibitors in LCH. © 2015 Wiley Periodicals, Inc.